Real‐Time Changes in Arctic Ice Presented in Online Portal. (29th October 2013) - Fausto, Robert S.; Colgan, William; Langen, Peter L.
<x xml:space="preserve">Abstract</x> The contemporary Arctic cryosphere is in a highly transient state, responding to a persistent and accelerating climate forcing. Over the past decade, the frequency with which annual ice losses in Greenland reached record highs and annual sea ice area in the Arctic reached record lows has been exceptional: Each year, the Greenland ice sheet has lost roughly as much ice, if melted, to fill most of Lake Erie, and since 2007, all sea ice minima have been smaller than those seen between 1979 and 2006. The anticipated consequences of cryospheric change, including more solar radiation absorbed by newly exposed patches of seawater where there once was ice and substantial sea level rise thanks to melting glaciers, provide a strong motivation to understand the state of Arctic ice.